2007
DOI: 10.1097/dbp.0b013e3181132074
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Maternal Chronic Illness on Child Well-Being in Single Parent Families

Abstract: Several areas for future work on how illness affects single-parent families were identified such as prospectively studying illnesses with a variable course and determining which protective factors promote resiliency for children in this difficult situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
4
16
0
1
Order By: Relevance
“…The oral administration of the test items and our use of raw (rather than age-normed) scores may have mitigated these concerns, but it remains possible that the obtained findings regarding child-reported depressive symptoms were biased by this assessment limitation. Although the comparable consistency of our obtained reports with other age-appropriate samples (O'Brien et al, 1997;Wampler et al, 2002), as well as the prior use of the CDI with very young children (Annunziato et al, 2007;Biggar & Forehand, 1998) bolsters our confidence in the current findings, they must be interpreted with caution in light of this limitation. Second, the current measures of expressed aggression, inhibitory control, and, to a lesser extent, narrative representation, await further validation across racial/ethnic groups.…”
Section: Strengths and Limitationssupporting
confidence: 47%
See 1 more Smart Citation
“…The oral administration of the test items and our use of raw (rather than age-normed) scores may have mitigated these concerns, but it remains possible that the obtained findings regarding child-reported depressive symptoms were biased by this assessment limitation. Although the comparable consistency of our obtained reports with other age-appropriate samples (O'Brien et al, 1997;Wampler et al, 2002), as well as the prior use of the CDI with very young children (Annunziato et al, 2007;Biggar & Forehand, 1998) bolsters our confidence in the current findings, they must be interpreted with caution in light of this limitation. Second, the current measures of expressed aggression, inhibitory control, and, to a lesser extent, narrative representation, await further validation across racial/ethnic groups.…”
Section: Strengths and Limitationssupporting
confidence: 47%
“…Items were summed to yield a total depression score. The CDI has been standardized for children ages seven to 17 (Kovacs, 1992), though it has been used at younger ages (Annunziato, Rakotomihamina, & Rubacka, 2007;Biggar & Forehand, 1998). Because the current study employed the CDI at age six when age-normed scores were not available, raw scores were used in these analyses.…”
Section: Depressive Symptomsmentioning
confidence: 99%
“…While there is considerable uncertainty about maternal physical health and child welfare, there is evidence to suggest that the illness of mothers negatively impacts the health of their offspring. 7, 10, 14, 58 Moreover, recent research, utilizing the same sample of mothers, children and households, and the same measures of maternal physical and mental health, demonstrates an independent association between both maternal mental and physical health and child mental health. 59 Also, similar to this study, that study demonstrated that even in the absence of maternal smoking, children’s mental health was worse in households with adult smokers and the more smokers present, the worse the child’s mental health.…”
Section: Discussionmentioning
confidence: 94%
“…This suggests that the target groups may be resilient in terms of the salivary cortisol reactivity to chronic stressors. Accordingly, qualitative studies [34] and quantitative studies [35,36] proposed that the target groups function well and may be resilient. In addition, none of the adolescents showed a cortisol ratio below one, suggesting that the target groups displayed a healthy diurnal cortisol pattern [11].…”
Section: Discussionmentioning
confidence: 99%